2013
DOI: 10.1016/j.jamcollsurg.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Surgical Resection and Survival among Elderly Patients with Poor Prognosis Cancer

Abstract: Background Reports indicate that blacks have lower survival following the diagnosis of a poor prognosis cancer, compared with whites. We explored the extent to which this disparity is attributable to the underuse of surgery. Study Design Using the SEER-Medicare database we identified 57,364 patients, ages ≥65, with a new diagnosis of non-metastatic liver, lung, pancreatic and esophageal cancer, from 2000-2005. We evaluated racial differences in resection rates after adjustment for patient, tumor and hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Using SEER-Medicare data from 2000 to 2007, Revels et al reported that only 29 % of patients underwent surgery surgical resection for locoregional pancreatic cancer. 4 Similarly, using data from the National Cancer Data Base from 1995 to 2004, Bilimoria et al 15 found that even among patients with stage I pancreatic cancer, only 26.8 % underwent resection. After excluding patients with severe medical comorbidities and patients who refused surgery, 52 % of patients with stage I disease still did not undergo resection.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Using SEER-Medicare data from 2000 to 2007, Revels et al reported that only 29 % of patients underwent surgery surgical resection for locoregional pancreatic cancer. 4 Similarly, using data from the National Cancer Data Base from 1995 to 2004, Bilimoria et al 15 found that even among patients with stage I pancreatic cancer, only 26.8 % underwent resection. After excluding patients with severe medical comorbidities and patients who refused surgery, 52 % of patients with stage I disease still did not undergo resection.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies based on large national databases have demonstrated that black patients in the general population are less likely to undergo surgical resection and less likely to receive adjuvant therapy for locoregional PDAC than white patients. [2][3][4][5][6]9,15 Murphy et al demonstrated that black patients with locoregional pancreatic cancer are less likely to see a medical oncologist, radiation oncologist, and surgeon, and are less likely to receive surgery and chemotherapy. 6 We did not observe these treatment disparities among patients treated in the DoD health care system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 More recently, Revels et al reported that elderly black patients are less likely to undergo surgery after diagnosis of several poor prognosis cancers, including esophageal cancer, regardless of the resection rate of the treating hospital. 19 Reasons for this disparity are still not fully understood, yet it should not be forgotten that surgery remains the mainstay for treatment of esophageal cancer and can drastically modify the natural history of the disease. Therefore, efforts should be made to individuate and remove obstacles towards equal access to the best treatment across races.…”
Section: Discussionmentioning
confidence: 99%